Proceso de atención de enfermería escolar en alteración del patrón nutricional-metabólico del 2do año "A" Escuela Julio María Matovelle. - Quezada Cuenca, Mirian Beatriz (2014)
This research paper “Process school care nursing altered nutritional -metabolic pattern of 2nd year “A " school Matovelle Julio Maria " is part of Macroproyecto " nursing process with implementation of school nurse to the good life " . It was established as a general objective: to implement the nursing process with taxonomic interrelationship NANDA -NIC- NOC , 2012-2014 ; specific objectives : to identify altered functional patterns in children of the 2nd year "A" , the July school Mary Matovelle as Marjory Gordon model and determine more frequent nursing diagnoses for each altered pattern , applying NANDA -NIC- NOC taxonomy. A descriptive study was developed with the intervention, the total population was 498 students and the sample consisted of 28 children / as. The techniques and instruments used were interview, observation and guidance of each instrument. Model Marjory Gordon has 11 functional patterns was used to assess the process of nursing care, after the collection and organization of data were tabulated to select or patterns that require immediate attention , resulting in the alteration nutritional - metabolic pattern . The results show that 42.85 % have excess nutritional imbalance , the 39.28 % practice sedentary activities like watching television and playing video games, 35.72 % have long-term risk of complications METABOLIC and 78.57 % have oral problems (caries and halitosis ) . Keywords: nursing process, Marjory Gordon model, metabolic nutritional pattern.